1991
DOI: 10.1159/000116672
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ‘Lost Time’ on the Outcome of Epilepsy

Abstract: A review of a series of epileptic patients revealed the importance of the ‘lost time’ in the future time course of a patient. The ‘lost time’ is regarded as the period of time elapsed since the onset of symptoms and the implementation of adequate treatment. An assessment of the follow-up of 3,529 epileptic patients showed that the shorter the ‘lost time’, the greater the efficacy of anticonvulsant treatment. Even the incidence of relapses after discontinuation of antiepileptic drugs correlates with the ‘lost t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Based on a meta-analysis of the literature, 1 the risk of relapse after drug withdrawal was 25% at 1 year and 29% at 2 years. Several factors have been implicated in the risk of relapse, including age at onset of seizures, 2-7 age at treatment withdrawal, 5 8-11 family history of epilepsy, 5 12-14 recognised aetiology of epilepsy or abnormal neurological or psychiatric findings, 5 8 9 13-18 EEG abnormalities, 7 10 14- 16 18-22 number of seizures preceding remission, 2 8 9 11 13 15-17 23 24 and duration of seizure free period on treatment. 11 12 16 25 The risk of seizure relapse attributable to drug discontinuation is less well defined.…”
mentioning
confidence: 99%
“…Based on a meta-analysis of the literature, 1 the risk of relapse after drug withdrawal was 25% at 1 year and 29% at 2 years. Several factors have been implicated in the risk of relapse, including age at onset of seizures, 2-7 age at treatment withdrawal, 5 8-11 family history of epilepsy, 5 12-14 recognised aetiology of epilepsy or abnormal neurological or psychiatric findings, 5 8 9 13-18 EEG abnormalities, 7 10 14- 16 18-22 number of seizures preceding remission, 2 8 9 11 13 15-17 23 24 and duration of seizure free period on treatment. 11 12 16 25 The risk of seizure relapse attributable to drug discontinuation is less well defined.…”
mentioning
confidence: 99%
“…Alternatively, Lee et al [2] have suggested that the late onset of seizures in card game-induced reflex epilepsy reflects a phenotypic difference in the clinical spectrum of idiopathic generalized epilepsy. They insisted that card game-induced reflex epilepsy might be another type of adult-onset idiopathic generalized epilepsy, which was supported usually by normal interictal EEG findings in both adult-onset idiopathic generalized epilepsy and card game-induced reflex epilepsy [2,31] . Goossens et al [27] also reported 15 patients with card game-induced reflex epilepsy who mostly had generalized spike, spike-wave, or poly-spikewave discharges in EEG and seizures consisted of myoclonus, absences, and generalized convulsions, and they suggested that the clinical and EEG findings supported the diagnosis of primary generalized epilepsy.…”
Section: Discussionmentioning
confidence: 97%
“…There is no consensus on the mode of withdrawal. Tapering of AEDs ranges from rapid withdrawal to slow withdrawal spread over a period of two years (Bouma 1987;Duncan 1987;Oller-Daurella 1975;Overweg 1981;. In other studies, the tapering period has come down to three to six months, reflecting a di erent clinical approach (Arts 1988;Callaghan 1988;Emerson 1981;MRC 1991;Tennison 1994), but as yet there is no consensus in this tapering regimen.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%